Energy and glacier mass balance of Fürkeleferner, Italy: past, present, and future - Krampe, Daniela; Arndt, Anselm; Schneider, Christoph (Frontiers in Earth Science, 2022)
The energy and mass balance of mountain glaciers translates into volume changes that play out as area changes over time. From this, together with former moraines during maximum advances, information on past climate conditions and the climatic drivers behind during glacier advances can be obtained. Here, we use the distributed COupled Snowpack and Ice surface energy and mass balance model in PYthon (COSIPY) to simulate the present state of an Italian glacier, named Fürkeleferner, for the mass balance years 2013 to 2017. Next, we investigate the local climate during the time of the last ``Little Ice Age'' (LIA) maximum glacier advance using COSIPY together with the LIA glacier outline retrieved from moraine mapping and a digital elevation model (DEM) adapted for the glacier’s geometry at the time of the LIA as a benchmark. Further, the glacier’s sensitivity to future air temperature rise of \SI{+1}{K} and \SI{+2}{K} is investigated using the same model. For all simulations, meteorological data of closely located climate stations are used to force the model. We show the individual monthly contribution of individual energy and mass balance components. Refreezing during the summer months is an important component of the energy and mass balance, on average about \SI{9}{\percent} relative to total annual ablation. The results from simulating past climate show a 2.8 times larger glacier area for F\"urkeleferner during the LIA than today. This further implies a \SI{2.5}{K} colder climate, assuming that the amount of precipitation was \num{10}--\SI{20}{\p} in excess of today's value. Concerning further temperature rise of \SI{2}{K} the glacier would only consist of ablation area implying sustained mass loss and eventual total mass loss. Even under current climate conditions, the glacier area would have to decrease to \SI{17}{\percent} of its current area to be in steady state. We discuss the reliability of the results by comparing simulated present mass balance to measured mass balances of neighbouring glaciers in the European Alps and with short-term measurements on Fürkeleferner itself. In conclusion, we are able to show how the glacier responds to past and future climate change and determine the climatic drivers behind.